A Novel Type of Neuron Within the Dorsal Striatum - Mao, Miaomiao; Nair, Aditya; Augustine, George J. (Frontiers in Neural Circuits, 2019)
The striatum is predominantly composed of medium spiny projection neurons, with the remaining neurons consisting of several types of interneurons. Among the interneurons are a group of cells that express tyrosine hydroxylase (TH). Although the intrinsic electrical properties of these TH-expressing interneurons have been characterized, there is no agreement on the number of TH-expressing cell types and their electrical properties. Here we have used transgenic mice in which YFP-tagged channelrhodopsin-2 was expressed in putative TH-expressing cells in a Cre-dependent manner. We found that the YFP+ neurons in the striatum were heterogeneous in their intrinsic electrical properties; unbiased clustering indicated that there are three main neuronal subtypes. One population of neurons had aspiny dendrites with high-frequency action potential firing and plateau potentials, resembling the TH interneurons (THIN) described previously. A second, very small population of labelled neurons resembled MSN. The third population of neurons had dendrites with an intermediated density of spines, showed substantial action potential adaptation and generated prolonged spikes. This type of striatal neuron has not been previously identified in the adult mouse and we have named them Frequency-Adapting Neurons with Spines (FANS). Because of their distinctive properties, FANS may play a unique role in striatal information processing.